Mare nostrum : desafios e perspectivas da realidade marítima à teologia - Pinto, Raphael Colvara (2019)
The concept of “place” as defined by maritime reality, far from being either liberating or alienating, has an ambivalent character that needs to be described; it is not only an abstract flow vector, described by the anthropologist Marc Augé as the concept of “non place”, but it is also a place where the tensions between economic globalization and uniqueness of a culture are challenged. Historically considered as an environment of interaction between political, military and economic interests, the seas and oceans have become intense places of connection and mobility. This concept has survived the different historical scenarios of colonial thought which, during the maritime expansion period of the fifteenth century, globalized European culture to the detriment of others regarded as ‘primitive’. This situation, called Modernity, has a hidden face: colonialization as a civilizing project; from this, we propose a bibliographic review, presenting as an approach, evidence of the patterns of “colonial power” from the time of maritime expansion to contemporary globalization. The research question is: Is the legacy of colonial thought intrinsic to modernity or one of its consequences? What is the place of the maritime reality when one wants to propose a non-dominance of theological thought, where religion itself has sacralized violence and imperialism? From this context we seek to present a theoretical-critical framework of the role that epistemological knowledge of modernity played a role in the perpetuation of European dominance, outlining the basic principles from an interface between Theology and the Social Sciences; we will focus on the sea as a theological “place”, the hypothesis being that the seas and oceans are not only vectors of colonial hegemony and a space for transport of commodities, but also a distinct way of being in the world, especially for those who live and work in this reality. Its transitory character carries a presence in regard to the people living at sea and –at the same time – also absence and anonymity, understood as invisibility. The final proposal is to build bridges, realizing that the seas have the potential to both integrate and exclude. Here we will call it “maritimity”, that is, the alternate “place”, as well as the environment where Jesus cast the nets for his Messianic project.